Hybrid solar and heat-driven district cooling system: Optimal integration and control strategy. (1st May 2019) - Sameti, Mohammad; Haghighat, Fariborz
Highlights: Proposed an MILP model for integration of heating sides and cooling sides. Optimal combination of heating and cooling equipment as well as the network. Investigation of the effect of cold and hot thermal energy storage on cost and emission. A comparison among conventional, heat-driven, solar-driven, and hybrid generations. Analysis of cooling distribution network, electrical network, and grid interaction. Abstract: An optimal design and well-scheduled district cooling system is crucial for the success of the implementation of such systems especially when the cooling plant(s) are intended to be connected to a group of newly-built consumers. In order to supply such customers the required cooling load, a huge capital and operation investment in district cooling network is a necessity if the cooling network is separated from the heating production units. One solution scheme is to take advantage of the heating generation units, which are off during summer to drive the cooling equipment. However, among various design parameters, the most important one is the desirable configuration of the district of interest: best selection and combination of the heating and cooling generation equipment. A least-annualized-cost mathematical approach based on the mixed integer linear programming (MILP) is described in this paper to determine the optimal integration as well as the optimal control of the flow and the storage. The test case study showed that the methodology was effective to give a huge savings in both total annual cost and emission for a wide range of designs. More than 67% of CO2 emission reduction is achieved through the hybrid heat and solar-driven arrangement.